Da alienação constituída à alienação constitutiva: pensando o lugar da ideologia em Slavoj Žižek (Revista Eletrônica Estudos Hegelianos, 2019)
The aim of this paper is to discuss Žižek’s proposal to understand ideology as something that works analogously to the psychoanalytic conception of fantasy, as it has been elaborated by Jacques Lacan, a French psychoanalyst strongly influenced by Hegelian thought. By taking into account the issue of intersubjectivity, our paper aims to investigate how this last one is reallocated in order to think of relations between desire and ways of being as factors that determine the unavoidable feature of the alienation. However, the treatment of alienation, as a problem which is intrinsic to capitalist ideology, requires a discussion which enables the distinction and the relation between two kinds of alienation: a constituted and a constitutive one. By following this approach, which is also endorsed by Žižek, an alternative critical thinking against capitalism ideology may be promoted.